2018
DOI: 10.1039/c8ra01583j
|View full text |Cite
|
Sign up to set email alerts
|

The formulation and characterization of 3D printed grafts as vascular access for potential use in hemodialysis

Abstract: An arteriovenous graft that was successfully 3D printed with a novel printing ink formulation that displayed excellent mechanical and anti-fouling properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It has been shown that, among cylindrical, twisted, and hexagonal designs of the outer rim of the 3D printed tubular grafts, the twisted design is more stable due to a better fusion of the layers. 61 Kinking of U shape small diameter vascular grafts in vivo precludes future clinical application. Therefore, designing the biodegradable vascular grafts with a corrugated structure can reduce the risk of kinking.…”
Section: Vascular Graftsmentioning
confidence: 99%
“…It has been shown that, among cylindrical, twisted, and hexagonal designs of the outer rim of the 3D printed tubular grafts, the twisted design is more stable due to a better fusion of the layers. 61 Kinking of U shape small diameter vascular grafts in vivo precludes future clinical application. Therefore, designing the biodegradable vascular grafts with a corrugated structure can reduce the risk of kinking.…”
Section: Vascular Graftsmentioning
confidence: 99%
“…Therefore, a combination of the two may be another option. In a variety of techniques for skin constructs, the processing methods mainly consist of 3D printing, 45 electrospinning, 46 freeze drying, 47 etc . The choice of this process should satisfy scaffolds with high porosity and appropriate pore sizes.…”
Section: Fabrication Approaches For Prevascularized Skinmentioning
confidence: 99%
“…Thus, there are various studies demonstrating the potential of 3D printed acrylate copolymers and acrylic polymers using the DLP system for vascular applications. Cheng et al 71 examined two different acrylate copolymers for arteriovenous graft (AVG) applications. Modified 4-acryloylmorpholine (ACMO) with trimethylolpropane triacrylate (TMPTA) and trimethylolpropane ethoxylate triacrylate (TMETA) was used as a 3D printing ink and PEGDA was used as a control material.…”
Section: Conventional Strategy For Developing Vascular Constructsmentioning
confidence: 99%